The Libertarian-Legal Concept of Law - Shukuryan, Armen (NAS RA)
The essence and substantive features of the libertarian-legal concept were thoroughly analyzed in the article. The author of this concept is the world-famous scientist, Academician of the Russian Academy of Sciences, V. S. Nersesyants. According to this concept, law, and rights, as well as legal law and non-legal law, are distinguished. The libertarian conceptual approach assumes all possible forms of differentiation and correlation between natural law and positive law, from separation and conflict between them to their overlap (legal law).
Keywords: Legal Studies